Hubungan Perilaku Cuci Tangan Pakai Sabun Dengan Kejadian Diare Pada Anak Usia Sekolah Di SD Negeri 19 Kota Bengkulu Tahun 2026 - Dina Anggraini; Meri Epriana Susanti; Erlina Panca Putri (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Diarrhea is an inflammation of the gastric and small intestinal mucosa, resulting in abnormal stools with a soft, liquid, or watery consistency, occurring more than three times a day. In Indonesia, the number of diarrhea cases receiving health care across all age groups reached 3,056,072. The purpose of this study was to determine the relationship between handwashing with soap and diarrhea incidence in school-aged children at SD Negeri 19, Bengkulu City, in 2026. The research method used was a descriptive study with a cross-sectional approach. The sampling technique used Proportionate Stratified Random Sampling, with the sample size calculated using the Slovin formula, totaling 64 school-age children at SD Negeri 19, Bengkulu City, in 2026. The chi-square test results showed a p-value of 0.000, indicating a relationship between handwashing with soap and diarrhea incidence among school-age children at SD Negeri 19, Bengkulu City, in 2026. The results of this study are expected to be used to develop a coaching and counseling program related to handwashing with soap and diarrhea incidence among school-age children at SD Negeri 19, Bengkulu City.